An Empirical Analysis of the Effects of Stakeholder Management on Construction Project Delivery: Case-Study of the Construction of Access Bank Head Office - Adukwei Habada, Wilhermina (2021)
A Postgraduate Thesis Submitted to the Department of Constructed Technology and Management of the Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of the requirement for the Award of a Degree of Master of Science in Project Management.